Rapid simultaneous acquisition of macromolecular tissue volume, susceptibility, and relaxometry maps. Issue 2 (4th September 2021) - Yu, Fang Frank; Huang, Susie Yi; Kumar, Ashwin; Witzel, Thomas; Liao, Congyu; Duval, Tanguy; Cohen‐Adad, Julien; Bilgic, Berkin
Abstract : Purpose: A major obstacle to the clinical implementation of quantitative MR is the lengthy acquisition time required to derive multi‐contrast parametric maps. We sought to reduce the acquisition time for QSM and macromolecular tissue volume by acquiring both contrasts simultaneously by leveraging their redundancies. The joint virtual coil concept with GRAPPA (JVC‐GRAPPA) was applied to reduce acquisition time further. Methods: Three adult volunteers were imaged on a 3 Tesla scanner using a multi‐echo 3D GRE sequence acquired at 3 head orientations. Macromolecular tissue volume, QSM, R 2 ∗, T1, and proton density maps were reconstructed. The same sequence (GRAPPA R = 4) was performed in subject 1 with a single head orientation for comparison. Fully sampled data was acquired in subject 2, from which retrospective undersampling was performed (R = 6 GRAPPA and R = 9 JVC‐GRAPPA). Prospective undersampling was performed in subject 3 (R = 6 GRAPPA and R = 9 JVC‐GRAPPA) using gradient blips to shift k‐space sampling in later echoes. Results: Subject 1's multi‐orientation and single‐orientation macromolecular tissue volume maps were not significantly different based on RMSE. For subject 2, the retrospectively undersampled JVC‐GRAPPA and GRAPPA generated similar results as fully sampled data. This approach was validated with the prospectively undersampled images in subject 3. Using QSM, R 2 ∗, and macromolecular tissue volume, the contributions of myelin and iron content to susceptibility were estimated. Conclusion: We have developed a novel strategy to simultaneously acquire data for the reconstruction of 5 intrinsically coregistered 1‐mm isotropic resolution multi‐parametric maps, with a scan time of 6 min using JVC‐GRAPPA.